(untitled) (Colloquia Comparativa Litterarum, 2025)
There is almost no empirical research into the later stages of classical singers’ careers and the difficulties faced. A quantitative study of operatic soloists was conducted via online questionnaire to ascertain when and how these difficulties manifest themselves. The survey divided the singers into 2 groups: those who stopped their solo careers as a result of the difficulties and those whose careers continued, in order to explore the differences between the responses of the 2 groups to the career downturn. This article posits that the singer’s crisis is a common experience, though one which singers seldom discuss amongst themselves. To illustrate this, it focuses on the 2 causes for career difficulties most often cited by the respondents: mental health issues and technical vocal problems. The study demonstrates a reluctance by singers to deal with anxiety, stress and self-doubt, even at the cost of their careers.